Highly Efficient and Stable Perovskite Solar Cells Using a Dopant‐Free Inexpensive Small Molecule as the Hole‐Transporting Material. Issue 23 (21st June 2018) - Li, Yong; Scheel, Kyle R.; Clevenger, Robert G.; Shou, Wan; Pan, Heng; Kilway, Kathleen V.; Peng, Zhonghua
Abstract: The hole transporting layer (HTL) plays an important role in realizing efficient and stable perovskite solar cells (PSCs). In spite of intensive research efforts toward the development of HTL materials, low‐cost, dopant‐free hole transporting materials that lead to efficient and stable PSCs remain elusive. Herein, a simple polycyclic heteroaromatic hydrocarbon‐based small molecule, 2, 5, 9, 12‐tetra( tert ‐butyl)diacenaphtho[1, 2‐ b :1′, 2′‐ d ]thiophenen, as an efficient HTL material in PSCs is presented. This molecule is easy to synthesize and inexpensive. It is hydrophobic and exhibits excellent film‐forming properties on perovskites. It has unusually high hole mobility and a desirable highest occupied molecular orbital energy level, making it an ideal HTL material. PSCs fabricated using both the n‐i‐p planar and mesoscopic architectures with this compound as the HTL show efficiencies as high as 15.59% and 18.17%, respectively, with minimal hysteresis and high long term stability under ambient conditions. Abstract : A polycyclic heteroaromatic hydrocarbon based small molecular semiconductor is employed as a dopant‐free and potentially cost‐effective hole‐transporting material in the production of perovskite solar cells. Perovskite solar cells featuring this hole‐transporting material, fabricated on top of a simple methylammonium lead iodide active layer, demonstrate power conversion efficiencies over 18% and good stability under ambient conditions.